Optimization of Process Conditions for Hydrogenation of Waste Oil. Issue 3 (May 2019) - Ji, Sheng-hao; Gui-zhou, Gu; Hu, Xiu-bo; Dan, Li; Song, Xin-yang
Abstract: Ni/SiO2 -γ-Al2 O3 catalyst was prepared by co-impregnation method, study on the performance change of hydrofining product oil, get the optimum process conditions for hydrofining waste oil. The results showed that the hydrogenation effect of waste oil hydrofining was better under the conditions of reaction temperature 250°C, hydrogen pressure 7.9 MPa, space velocity 0.5h −1 and hydrogen oil volume ratio 1000-1200: 1. The bromine value of the oil was 0.18gBr/(100g oil), the residual carbon was 0.012, the sulfur content was 0.37 ug/g, the colorimetric value was less than 0.5, and the freezing point was -37°C, kinematic viscosity had almost no loss, the performance of waste oil after hydrogenation had been greatly improved.